IMPLEMENTATION OF THERMOCHEMISTRY LEARNING VIDEO FOR GRADE XI STUDENTS - Ninis Khairunnisa; Ibnu Khaldun; Erlidawati Erlidawati (Chimica Didactica Acta, 2020)
A research has been conducted entitled "The Application of Thermochemistry Learning Videos for Class XI MIA-I MAN 6 Aceh Besar Students". The purpose of this study was to analyze student activities, learning outcomes, and student responses after the application of thermochemistry learning video in class XI MIA-I MAN 6 Aceh Besar. This study uses an approach with a descriptive type of research. The sample in this study were students of class XI MIA-1 MAN 6 Aceh Besar. The results show participant activity increased significantly as seen in the percentage of activity from the first meeting to the fourth meeting in a row, which was 76.52%; 83.33% ; 85.83% and 92.42%. Learning outcomes increased and achieved classical completeness as seen from the percentage of complete learning outcomes, which was 88%. The response of students to the application of learning video media on thermochemical material also showed a positive response with a percentage of 88.2%. Thus, it can be said that student learning outcomes through the application of learning video media have increased and have taken place classically, student activities have also increased at each meeting, and students have responded positively to the application of learning video media.